2009
DOI: 10.1158/1055-9965.epi-09-0446
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to High Molecular Weight Allergens and Lymphoma Risk Among Italian Adults

Abstract: Objectives. Exposure to high molecular weight (HMW) allergens that provoke immune reactivity through an IgE-mediated pathway has been associated with a decreased risk of B-cell lymphoma. The present analysis was conducted to assess the associations between occupational exposure to specific HMW allergens and the risk of B-cell, T-cell, and Hodgkin's lymphomas. Methods. We analyzed data from 2,290 incident lymphoma cases and 1,771 population-based controls enrolled in a multicenter study of hematolymphopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…There have been several investigations regarding definition and measurement of allergies and the subtypes of HM assessed, however, an inverse association with history of allergies has been reported for HM as a group [4], lymphoma overall [5,6], Hodgkin's lymphoma (HL), Non Hodgkin lymphoma (NHL) [7][8][9][10], Acute Lymphoblastic Leukemia (ALL) [11,12], and multiple myeloma (MM) [13] (Table 1) [14]. The study indicates a moderately increased risk of HMs in women but not in men with a history of allergies to airborne allergens, especially to plants, grass, or trees.…”
Section: Allergy and Hematologic Malignanciesmentioning
confidence: 99%
“…There have been several investigations regarding definition and measurement of allergies and the subtypes of HM assessed, however, an inverse association with history of allergies has been reported for HM as a group [4], lymphoma overall [5,6], Hodgkin's lymphoma (HL), Non Hodgkin lymphoma (NHL) [7][8][9][10], Acute Lymphoblastic Leukemia (ALL) [11,12], and multiple myeloma (MM) [13] (Table 1) [14]. The study indicates a moderately increased risk of HMs in women but not in men with a history of allergies to airborne allergens, especially to plants, grass, or trees.…”
Section: Allergy and Hematologic Malignanciesmentioning
confidence: 99%
“…Two studies reported a reduced risk of lymphoma among those with occupational allergen exposures (24, 25), although a previous investigation in Spain found no association (26). These studies did not assess the relationship between allergy symptoms and lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…Inverse associations have been reported in case- control and cohort studies of glioma [26], [27], meningioma [28], [29], non-Hodgkin’s lymphoma [30], leukemia [31], and pancreatic cancer [32]. However, a history of asthma has been positively associated with lung cancer [33], and results for all cancers combined are unclear [34], [35].…”
Section: Discussionmentioning
confidence: 99%